An Efficient Algorithm for Energy Management in Wireless Sensor Networks via Employing Multiple Mobile Sinks. (18th January 2016) - Shi, Jiugen; Wei, Xing; Zhu, Wei
Abstract : Energy saving in wireless sensor networks is a fundamental issue as most sensor nodes are powered by batteries. The deployment of mobile sinks can alleviate the imbalance of energy consumption among sensor nodes, thereby prolonging the network lifetime. In this paper, we study the energy management problem in sensor networks, using multiple mobile sinks. We first formulate the problem as a novel data collection problem and then propose an efficient algorithm for it. The key challenge in the design of the proposed algorithm is how to balance the workload among mobile sinks and the energy consumption among sensor nodes through the control of the movement of mobile sinks. We finally evaluate the performance of the proposed algorithm through experimental simulation. Experimental results show that the proposed algorithm is very promising, which can improve the energy efficiency and the quality of data transmission in the sensor network significantly.